2011
DOI: 10.1186/1471-2350-12-36
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in genes controlling inflammation and tissue repair in rheumatoid arthritis: a case control study

Abstract: BackgroundVarious cytokines and inflammatory mediators are known to be involved in the pathogenesis of rheumatoid arthritis (RA). We hypothesized that polymorphisms in selected inflammatory response and tissue repair genes contribute to the susceptibility to and severity of RA.MethodsPolymorphisms in TNFA, IL1B, IL4, IL6, IL8, IL10, PAI1, NOS2a, C1INH, PARP, TLR2 and TLR4 were genotyped in 376 Caucasian RA patients and 463 healthy Caucasian controls using single base extension. Genotype distributions in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 49 publications
5
50
0
1
Order By: Relevance
“…Some studies have reported a positive association of TNF-α -308 alleles with RA 3,16,31-34 while others have reported lack of association with RA. 36,[48][49][50][51][52] In conformity with the majority of previous studies, the present study failed to demonstrate any association between the TNF-α -308 G>A promoter polymorphism and RA in cohort 1. Interestingly, the comparison between RA patients who were RF positive and RF negative revealed a marginally significant difference in the allele frequencies (p=0.05, OR=2.86, 0.96-8.52 at 95% CI).…”
Section: Discussionmentioning
confidence: 31%
See 2 more Smart Citations
“…Some studies have reported a positive association of TNF-α -308 alleles with RA 3,16,31-34 while others have reported lack of association with RA. 36,[48][49][50][51][52] In conformity with the majority of previous studies, the present study failed to demonstrate any association between the TNF-α -308 G>A promoter polymorphism and RA in cohort 1. Interestingly, the comparison between RA patients who were RF positive and RF negative revealed a marginally significant difference in the allele frequencies (p=0.05, OR=2.86, 0.96-8.52 at 95% CI).…”
Section: Discussionmentioning
confidence: 31%
“…The frequency in the control population of Punjab (cohort 1) was 8.3%, which was similar to Chinese (7.7%) 3 and Czech (9.7%), 10 and higher than Japanese (3.3%), Egyptian (3.1%) populations, and the North Indian (4.9%) population from Uttar Pradesh. [32][33][34] The frequency in cohort 2 comprising the Jammu and Kashmir population (25%) was nearly similar to that reported in European populations including North Swedish (24%), 19 Dutch (23.8%), 35 and Netherlands (19%) 36 but lower than Saudi Arabian (31.0%) 28 population. The frequency of A allele in Jammu and Kashmir was higher compared to the population of Punjab.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Clinical characteristics such as age at onset, RF positivity, joint erosion and extra-articular manifestations were compared among patients, and it was found that patients with IL-8 3'-UTR 2767AA genotype had a significantly younger age of onset of RA than patients without that genotype [118] . In caucasian RA patients and healthy controls the 781 C/T (2227306) SNP of IL-8 gene was examined with the result that CC genotype is associated with the early onset of RA [137] .…”
Section: Il-8mentioning
confidence: 99%
“…IL1B is 7020 bp in length and contains 826 polymorphisms according to the NCBI dbSNP database. Among them, IL1B-31 [10][11][12][13][14], IL1B-511 [9][10][11][14][15][16][17][18][19][20][21][22][23][24][25][26] and IL1B + 3954 [9][10][11]14,[16][17][18][19][20][21][22][23][25][26][27][28][29] are the most studied in the association with RA.…”
Section: Introductionmentioning
confidence: 99%